Attitudes and Linguistic Orientations in Iceland: The Role of Attitudes and Orientations in Learning and Using Icelandic and English in Iceland - Birkir Már Viðarsson 1992- (2018)
Adults in Iceland who have a native language that is not Icelandic vary widely in their proficiency in Icelandic. This study sought to examine factors that might influence these individual differences, with a particular interest in the role of English as a lingua franca in Iceland, along with attitude and motivation to learn and use Icelandic and English. While the study was particularly interested in recruiting participants who possess low proficiency in Icelandic as well as in English (a group that is hard to reach and seldom participates in studies), a broader inclusionary criterion was employed in an attempt to include a range of proficiency levels. This criterion consisted of distribution of over 2.000 invitations to this study through compulsory schools in Reykjavík that were translated into multiple languages. The study itself involved a questionnaire constructed from a variety of sources as well as questions that were constructed for this study in order to examine the Icelandic social context in particular. The results of the study revealed that English plays an important role in the lives of individuals in Iceland whose native language is not Icelandic. Affective attitude was measured through a questionnaire by Dr. Elín Þöll Þórðardóttir (2015), and a more positive affective attitude was found towards English among the participants. However, participants who had a higher positive affective attitude towards Icelandic had lower self-perceived proficiency in English. Self-perceived proficiency was also higher among participants who had resided in Icelandic for longer and were more educated. Finally, questionnaires from Robert C. Gardner’s (1985) Attitude/Motivation Test Battery revealed that the participants were more instrumentally oriented towards learning and using English, but were more integratively oriented towards learning and using Icelandic.